China's Strategic Ambiguity on the Issue of Autonomous Weapons Systems - Pramudia, Putu Shangrina (UI Scholars Hub, 2022)
This paper discusses the factors behind China's ambiguous stance on the issue of autonomous weapons and its relationship with China's rise. In 2016 at the United Nations on Certain Conventional Weapons (UN-CCW), China was the only Permanent Five (P5) country to call for the prohibition and importance of a binding protocol on autonomous weapons. Through its position paper, China stated that the characteristics of autonomous weapons are not in accordance with the principles of International Humanitarian Law (IHL), fears of an arms race, to the threat of war. However, in 2017 China issued the New Generation of AI Development Plan (AIDP), which became the basis for China's development of autonomous weapons. This action violates their commitment at the UN-CCW because, through AIDP, China has planned the use, development, and production of autonomous weapons. Using the framework of the technologically innovative imperative and the conception of strategic ambiguity, this paper argues that China's ambiguous stance is a strategic intention resulting from a response to technological lag and systemic barriers that China is currently facing. This paper concludes that China's ambiguous stance is; (1) aimed to maintain the consistency of China's Peaceful Rise; (2) dealing with technologically innovative imperatives dynamic; (3) helping China in achieving China's Dream to achieve a Great Power status.